(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
Fungicidal effects of aqueous extract of Azadirachta indica plant parts (leaves, bark and roots) were determined on fungi that cause leaf spot of okra in Donga. In the study, the phytopathogenic fungi were isolated from infected okra leaves and identified based on morphological and cultural characteristics, namely: Cercospora abelmoschi and Cercospora malayensis, as confirmed by pathogenicity test using Koch’s postulate. Different concentrations (25, 50, 75 and 100 % w/v) of aqueous extracts of the leaves, bark and roots were separately added to growth media prior to inoculation (poisoned food method). All aqueous extracts of Azadirachta indica plant parts significantly (P < 0.05) reduced mycelia growth of the fungal pathogens and these effects gradually increased with increasing concentration. The highest inhibition was at 100% concentration, while the lowest inhibition percentage was observed at 25% concentration for each of the extracts. Statistically, there was a significant difference in the inhibition of radial growth in all the fungal isolates at all concentrations compared to the control. However, aqueous extracts of neem leaves were more effective on Cercospora abelmoschi with a higher inhibition percentage of 83.00% at 100% concentration, while aqueous neem root extracts had the lowest inhibition percentage of 25.13% at a concentration of 25% against Cercospora malayensis. It could be emphatically concluded that aqueous extracts of neem plant parts can effectively control fungal disease of okra leaves. This makes them potential biocides in disease control in that they are available, cheap, and safe.